2020
DOI: 10.3390/cancers12061674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGF2-Mediated Signaling in GIST—Promising Approach for Overcoming Resistance to Imatinib

Abstract: Inhibition of KIT-signaling is a major molecular target for gastrointestinal stromal tumor (GIST) therapy, and imatinib mesylate (IM) is known as the most effective first-line treatment option for patients with advanced, unresectable, and/or metastatic GISTs. We show here for the first time that the inhibition of KIT-signaling in GISTs induces profound changes in the cellular secretome, leading to the release of multiple chemokines, including FGF-2. IM increased migration, invasion, and colony formation of IM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The FGF2/R2 signaling has been extensively studied in GIST as a drug resistance mechanism. Sergei et al [ 54 ] and Boichuk et al [ 55 ] demonstrated that the blockage of FGFR2 signaling could enhance the responsiveness to DNA-Topoisomerase II inhibitors[ 54 ] while the downregulation of FGF2 signaling might stimulate the response to imatinib[ 55 ]. It’s contribution in GIST progression has been reviewed[ 56 ] but data about potential effects in GIST vascularization process are missing.…”
Section: Discussionmentioning
confidence: 99%
“…The FGF2/R2 signaling has been extensively studied in GIST as a drug resistance mechanism. Sergei et al [ 54 ] and Boichuk et al [ 55 ] demonstrated that the blockage of FGFR2 signaling could enhance the responsiveness to DNA-Topoisomerase II inhibitors[ 54 ] while the downregulation of FGF2 signaling might stimulate the response to imatinib[ 55 ]. It’s contribution in GIST progression has been reviewed[ 56 ] but data about potential effects in GIST vascularization process are missing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IM-resistance is the obstacle for trapping the further development of IM. Speci cally, more than 50% of patients with advanced and metastatic forms of the disease develop secondary resistance to IM-based therapy within 2 years after initiation of treatment [59]. It is widely known that IM is a successfully orally targeted drug, which metabolized by CYP 450 [60].…”
Section: Discussionmentioning
confidence: 99%
“…Massive secretion of the multiple chemokines, including FGF-2, was discovered to be induced by the imatinib c-KIT inhibition. Increased production of FGF-2 by GIST cells treated with imatinib activates the FGF-2/FGFR autocrine loop that presents a negative impact on the disease progression and might become one of the most important mechanisms underlying imatinib-resistance among some patients with GIST (30). Inhibition of FGF-signaling in imatinib-resistant patients was proved to restore their sensitivity to the applied treatment (31).…”
Section: Angiogenic Markersmentioning
confidence: 99%